Peningkatan Kemampuan Berhitung Permulaan Menggunakan Metode Bernyanyi Dengan Media Kartu Angka Pada Siswa Kelas I SD Negeri Ujung Tanah 2 Kota Makassar - Suci Rahmayani; Sukmawati; Ma’rup Ma’rup (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The main problem in this study is the low ability of students in starting arithmetic in addition and subtraction material.The purpose of this study was to improve student learning outcomes by using the singing method with number card media in addition and subtraction material in class I SD Negeri Ujung Tanah 2 Makassar City. This study uses the Classroom Action Research (CAR) method which includes planning, implementing actions, observing and reflecting. The location of this research was carried out at SD Negeri Ujung Tanah 2, Makassar City. The subjects in this study were class I students with a total of 23 students in the 2023/2024 academic year. The factors investigated are process factors and learning outcomes factors. The data that has been obtained from the results of the study were analyzed statistically descriptively used to describe student learning outcomes in addition and subtraction material using the singing method with number cards media.The results achieved in this study are: (1) There is an increase in student learning activities in each cycle. (2) In the first cycle, the average value of student learning outcomes was obtained, namely 60.1, while in the second cycle it was higher, reaching 93.4. In cycle I, there were 10 students or 43% who achieved learning completeness, while in cycle II there were 23 students or 100% who achieved learning completeness, this is because students have been able to solve addition and subtraction questions correctly by using the method singing and media cards. Based on the results of the research above, it can be concluded that the learning outcomes of initial numeracy skills through the singing method with number cards as media in addition and subtraction material in class I SD Negeri Ujung Tanah 2 Makassar City have increased.